The Influence of Bank Health Level Using the RGEC Method on Firm Value is Moderate by Company Size - Pratiwi, Suryaningtiyas Esti; Sulhan, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to determine the effect of bank health level using the RGEC method on firm value and to determine the ability of company size to moderate the effect of bank health on firm value in conventional banking companies listed on the Indonesia Stock Exchange in 2019-2022. This type of research is descriptive and quantitative with data analysis techniques using Moderated Regression Analysis (MRA) through SPSS (Statistical Program for Social Science) software. Sampling used a purposive sampling method and resulted in a sample size of 25 banks from 43 populations. The results showed that partially earning projected with ROA was able to influence the value of the company. Other research results show that company size can moderate the influence of earnings on firm value, which means that company size can strengthen the relationship between bank health and the value of conventional banking companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Not only that, bank health projected by NPL, GCG, and CAR shows the results there is no influence on firm value. Likewise, company size is unable to moderate the effect of NPL, GCG, and CAR on firm value.